2009
DOI: 10.4314/wsa.v33i3.49110
|View full text |Cite
|
Sign up to set email alerts
|

African leafy vegetables in South Africa

Abstract: In this article the term 'African leafy vegetables' was adopted to refer to the collective of plant species which are used as leafy vegetables and which are referred to as morogo or imifino by African people in South Africa. Function is central in this indigenous concept, which is subject to spatial and temporal variability in terms of plant species that are included as a result of diversity in ecology, culinary repertoire and change over time. As a result, the concept embraces indigenous, indigenised and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
64
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 11 publications
2
64
0
Order By: Relevance
“…South African food composition data (SAFCOD) tables (10) report the folic acid concentrations in raw samples of these vegetables respectively as 64, 346 and 141 mg/100 g fresh weight. The folic acid concentrations in raw leaves of other morogo vegetables such as amadumbe, black jack and nightshade (7) are respectively 126, 351 and 404 mg/100 g fresh Sample from Rustenburg*, Vhembe** and Capricorn***.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…South African food composition data (SAFCOD) tables (10) report the folic acid concentrations in raw samples of these vegetables respectively as 64, 346 and 141 mg/100 g fresh weight. The folic acid concentrations in raw leaves of other morogo vegetables such as amadumbe, black jack and nightshade (7) are respectively 126, 351 and 404 mg/100 g fresh Sample from Rustenburg*, Vhembe** and Capricorn***.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-growing DGLV, such as amaranth, spider flower and cowpea, feature prominently in this type of diet (7,18) . DGLV are important sources of food folate (11,12) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 This study was done during the rainy summer months, as most of the wild-growing species that are consumed grow in summer. 39 A study previously done at the rural KZN site showed that consumption of imifino (consumed during the first and last quarter of the year; summer) and spinach, mostly Swiss chard (consumed during the third quarter of the year; winter) complemented each other. 40 The authors therefore concluded that imifino should be promoted together with consumption of locally produced or commercially available spinach (a cool weather crop) to ensure a year-round consumption of darkgreen leafy vegetables to ensure a sustainable delivery of nutrients to these communities.…”
Section: Discussionmentioning
confidence: 99%